Tract Specificity in the Structure of Down Feathers of the Newly-Hatched Chick - Rawles, Mary E. (Proc Natl Acad Sci U S A, 1972)
Comparative study of completed down feathers from seven of the major tracts of newly-hatched Silver Campine chicks reveals tract-specific differences in the total length of the primary group of barbs and in the length of their barbule-free tips. Two classes of barbs can be distinguished on the basis of overall length in feathers of any one of the tracts: (a) those barbs that form from the first group (complement) of 9-11 barb ridges that arise in strict dorsoventral order around the circumference of the epidermal cylinder strict dorsoventral order around the circumference of the epidermal cylinder of the feather germ, and (b) those barbs that are added secondarily, later, either by the formation of a newly organized ridge between the bases of two of the original group of barb ridges, or by the splitting of one or more of the original complement of barb ridges. The primary (majority) group of ridges, only, are of use in gauging tract specificity. The statistical significance of measurements of total barb-length and the length of the barbule-free tips have been evaluated; differences between the feathers of each of the seven tracts examined can be distinguished statistically. The fact that the first feathers to form from the papillae are tract-specific shows, unquestionably, that specificity is present in the papillae from the very beginning of their organization, as might be inferred from their orderly pattern of origin in time and space within each of the various tracts. IMAGES: